2013
DOI: 10.5812/ircmj.7624
|View full text |Cite
|
Sign up to set email alerts
|

Co-administration of Grape Seed Extract and Exercise Training Improves Endothelial Dysfunction of Coronary Vascular Bed of STZ-Induced Diabetic Rats

Abstract: BackgroundOne of the known complications of diabetes mellitus is vascular dysfunction. Inability of the coronary vascular response to cardiac hyperactivity might cause a higher incidence of ischemic heart disease in diabetic subjects. It has been indicated that regular exercise training and antioxidants could prevent diabetic cardiovascular problems enhanced by vascular damage.ObjectivesThe aim of this study was to determine the effects of grape seed extract (as antioxidant), with and without exercise training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
0
9
0
1
Order By: Relevance
“…Considerable evidence indicates that endothelium‐dependent relaxation is impaired in diabetes mellitus . Impairment of endothelial function may contribute to the pathogenesis of cardiovascular complications induced by diabetes .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Considerable evidence indicates that endothelium‐dependent relaxation is impaired in diabetes mellitus . Impairment of endothelial function may contribute to the pathogenesis of cardiovascular complications induced by diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…Some of the mechanisms leading to these impairments in diabetes may include factors that decrease endothelium‐derived relaxation factors, such as NO and prostacyclin . It has been shown that endothelium‐derived NO is reduced in the diabetic milieu and that NO‐dependent vasodilation is reduced by oxidative stress, thereby impairing endothelial function . Nevertheless, conflicting results have been obtained in some studies reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In experimental diabetic rats, consumption of V. Vinifera seed was found to delay the onset and progression of cataract [14], protects the liver against destruction [15], protects the nerve against damage [16] and protects the hippocampus against apoptosis [17]. V. Vinifera seed was also found to improve coronary vascular function in diabetes [18]. Currently, protective effect of aqueous seed extract of V. vinifera (VVSAE) against pancreatic dysfunction in diabetes is unknown.…”
Section: Introductionmentioning
confidence: 97%